The Carbon Conundrum: A Systematic Analysis of Environmental Impacts in Large-Scale Cloud Computing Infrastructure - Vaibhav Haribhau Khedkar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the complex relationship between cloud computing infrastructure and environmental sustainability, analyzing challenges and opportunities in the rapidly evolving digital landscape. Through a comprehensive article review of current literature, industry reports, and case studies, we investigate four primary environmental concerns: energy consumption, carbon emissions, water usage, and electronic waste generation in cloud computing operations. The findings reveal that while data centers currently account for approximately 1% of global electricity consumption with a projected annual growth rate of 9%, emerging technologies and practices demonstrate promising potential for mitigation. The article identifies significant opportunities for environmental impact reduction through resource optimization, remote work enablement, and smart city integration, with virtualization technologies showing potential energy savings of 30-40% in typical deployments. The article proposes a framework for sustainable cloud computing that encompasses renewable energy adoption, circular economy principles, and innovative cooling solutions. The article concludes that while cloud computing poses substantial environmental challenges, strategic implementation of sustainable practices, technological innovation, and policy support can transform these challenges into opportunities for environmental stewardship in the digital age. These findings have important implications for cloud service providers, policymakers, and organizations pursuing digital transformation while minimizing ecological impact.
Keywords: Cloud Computing Infrastructure; Environmental Sustainability; Data Center Energy Efficiency; Digital Transformation; Green Computing